11.3k views
4 votes
23. Solve the following system by substitution.6x-6y= 12x - 7y = -4

User Ljedrz
by
4.3k points

1 Answer

5 votes

Step-by-step explanation

Given both equations:

(1) 6x-6y = 12

(2) x - 7y= -4

First, need to replace (1) in (2)

Isolating x for 6x - 6y=12 will give us:

Adding 6y to both sides:

6x-6+6y=12+6y

Simplifying:

6x= 12+6y

Dividing both sides by 6

6x/6=12/6 + 6y/6

Simplifying:

x=2+y

-Substituing x=2+y

2+y-7y = -4

Simplifying:

2-6y =-4

-Isolating y for 2-6y=-4:

-For x=2+y

Substitute y=1

x=2+1

Simplify

x=3

Finally, the solutions to the system of equations are:

x=3 , y=1

User Amrit Chhetri
by
4.6k points